Co-anchoring with the matrix clause: French verbal mood and German V2 - Truckenbrodt, Hubert (Proceedings of Sinn und Bedeutung, 2019)
In complement clauses, the French indicative and German V2 place similar semantic restrictions on their matrix verbs. In adjunct clauses, the French indicative and German V2 differ: French indicative adjunct clauses can be genuinely embedded, German V2 adjunct clauses cannot, and must follow their host clause. The analysis builds on a decomposed left periphery with Force > ... > Fin (Rizzi, 1997). The similarity in complement clauses is reduced to an attitudinal anchor [i] with a verbal mood feature in Fin, which is shared by the French indicative and German V2. The presupposition of this feature, due to Schlenker (2005), restricts the matrix verbs. The difference in adjunct clauses is argued to support a new mechanism for how the index [i] of this presupposition connects to the perspective holder in the matrix clause. Modifying a suggestion of Heim (2005), movement of Fin[i] to Force is argued to create a relative clause structure for perspective, interpreted by predicate abstraction. Where it occurs, it can take the matrix verb as its “external head”. For French, this leads to an account of embedded indicative adjunct clauses. In addition, the distribution of indicative vs. subjunctive in indefinite relative clauses (Farkas, 1985) is explained. For German V2, the restriction on adjunct clauses follows if German V2 is an overt instance of perspectival relative clause formation. This is connected to independently motivated properties of verb movement in V2-clauses, in an extension of the suggestions of Sode and Truckenbrodt (2018).